SINE LOGARITHMIC DISTANCE OF NEUTROSOPHIC REFINED SETS IN MEDICAL DIAGNOSIS - .A, Edward Samuel (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
In this paper, sine logarithmic distance among neutrosophic refined sets is proposed and some of its properties are discussed herein. The concept of the above method is an essential tool for dealing with uncertainties and shortcomings that affect the existing methods. Implementation of medical diagnosis is presented to find out the disease impacting the patient. Keywords:Neutrosophic set, neutrosophic refined set, sine logarithmic distance, medical diagnosis.